Superexpressão do receptor de Inositol 1,4,5-trifosfato isoforma 3 (ITPR3) em colangiocarcinoma e sua correlação com a proteína dependente de cálcio S100A4. - Ana Luiza Cosme Silva (2023)
Cholangiocarcinoma (CCA) is the second most malignant neoplasm in the liver that arises from the biliary tree. CCA is associated with a poor prognosis, and the key players involved in its pathogenesis are still not well understood. Receptor tyrosine kinases (RTKs), such as epidermal growth factor receptor (EGFR), can mediate intracellular calcium (Ca2+) signaling pathways via inositol 1,4,5trisphosphate (InsP3), activating inositol 1,4,5-trisphosphate receptors (ITPRs) and regulating tumor growth. ITPR isoform 3 (ITPR3) is the main intracellular Ca2+ release channel in cholangiocytes. The effects of intracellular Ca2+ are mediated by calciumbinding proteins such as Calmodulin and S100 calcium-binding protein A4 (S100A4). However, the clinicopathological and biological significance of EGFR, ITPR3 and S100A4 in CCA remains unclear. Thus, the present work investigates the immunoexpression of these three proteins in 59 CCAs from patients who underwent curative surgical treatment and correlates the data with clinicopathological features and survival. High ITPR3 expression was correlated with CA 19-9 levels, TNM stage and lymph node metastasis (N). Furthermore, ITPR3 expression was increased in distal CCA compared to control bile ducts and intrahepatic and perihilar CCAs. In summary, ITPR3 overexpression could contribute to CCA progression and it may represent a potential therapeutic target.